EVALUASI PRESERVASI DAN KONSERVASI BAHAN PUSTAKA DI DINAS PERPUSTAKAAN DAN KEARSIPAN KABUPATEN GIANYAR - I Gede Arya Winnata Suparta; Richard Togaranta Ginting; Kadek Aryana Dwi Putra (D3 Perpustakaan FISIP UNUD, 2025)
Preservation and conservation of library materials are carried out with the aim of saving the information contained in library materials at the Library and Archives Service of Gianyar Regency, so that they can still be used and avoid damage from various factors so that the collection can continue to be used by users for a long time. The approach used is qualitative descriptive, by collecting data through observation, interviews, and documentation. This study aims to identify weaknesses, obstacles, and challenges faced in the implementation of preservation and conservation activities of library materials at the Library and Archives Service of Gianyar Regency. The research findings show that the Library and Archives Service of Gianyar Regency experiences various challenges in efforts to preserve and conserve library materials, such as room temperature, sunlight, dust, insects, and humans that can damage the quality of library materials.